Asymmetric information as a cause for market failure - Application Service Providing (ASP) in Austria - Reiner Buchegger; René Riedl (Johannes Kepler University of Linz, Department of Economics, 2005)
The worldwide ASP market has not developed according to the forecasts of many market researchers. Asymmetric information, also known as quality uncertainty, has hardly been made the subject of discussion in the literature as a potential drawback for the successful development of the ASP market. Therefore, in this paper a theoretical framework is presented, showing three market situations with a varying amount of quality information on the customers' side and the resulting effects on the market situation and market development. Furthermore, the paper reports on empirical findings that show the existence of quality uncertainty on the Austrian ASP market.
Keywords: 330; Application Service Providing (ASP); ASP quality; ASP market; asymmetric information; quality uncertainty; adverse selection; attribute-based service quality measurement; web-based questionnaire; quality characteristics.; Asymmetrische Information; Dienstleistungsqualität; Branchenentwicklung; Österreich; Internetbasierter Dienst